(untitled) (African Journal of Biomedical Research, 2023)
Mitochondrial Permeability Transition (mPT) pore has become a target for the development of cytotoxic drugs that are relevant in situations of deregulated apoptosis. This study therefore investigated the effects of various fractions of the methanol extract of Ageratum conyzoides, a medicinal plant, on mPT pore. The methanol extract of Ageratum conyzoides (MEAC) was partitioned in succession between n-hexane, chloroform, ethylacetate and methanol. The fractions were concentrated at 40ºC to obtain chloroform (CFAC), ethylacetate (EFAC) and methanol (MFAC) fractions. Isolated rat liver mitochondria were exposed to the fractions. The opening of the pore, cytochrome c release, mitochondrial ATPase activity and lipid peroxidation were assessed spectrophotometrically. The study showed that all the fractions induced the opening of the pore with CFAC being the most potent. All the fractions caused cytochrome c release, enhanced mitochondrial ATPase activity and inhibited lipid peroxidation with CFAC having the highest effect. These findings therefore suggest that fractions of Ageratum conyzoides induce cytotoxicity in rat liver cells via mPT pore opening and also possess antioxidant property with CFAC being the most potent. The fraction will therefore be subjected to further study as this may be relevant in cases where apoptosis needs to be up regulated.